The impact of a radiologist‐led workshop on MRI target volume delineation for radiotherapy - Shivani Kumar; Lois Holloway; Dale Roach; Elise Pogson; Jacqueline Veera; Vikneswary Batumalai; Karen Lim; Geoff P. Delaney; Elizabeth Lazarus; Nira Borok; Daniel Moses; Michael G. Jameson; et al. (Journal of Medical Radiation Sciences, 2018)
Abstract Introduction Magnetic resonance imaging (MRI) is increasingly used for target volume delineation in radiotherapy due to its superior soft tissue visualisation compared to computed tomography (CT). The aim of this study was to assess the impact of a radiologist‐led workshop on inter‐observer variability in volume delineation on MRI. Methods Data from three separate studies evaluating the impact of MRI in lung, breast and cervix were collated. At pre‐workshop evaluation, observers involved in each clinical site were instructed to delineate specified volumes. Radiologists specialising in each cancer site conducted an interactive workshop on interpretation of images and anatomy for each clinical site. At post‐workshop evaluation, observers repeated delineation a minimum of 2 weeks after the workshops. Inter‐observer variability was evaluated using dice similarity coefficient (DSC) and volume similarity (VOLSIM) index comparing reference and observer volumes. Results Post‐workshop primary gross tumour volumes (GTV) were smaller than pre‐workshop volumes for lung with a mean percentage reduction of 10.4%. Breast clinical target volumes (CTV) were similar but seroma volumes were smaller post‐workshop on both supine (65% reduction) and prone MRI (73% reduction). Based on DSC scores, improvement in inter‐observer variability was seen for the seroma cavity volume on prone MRI with a reduction in DSC score range from 0.4–0.8 to 0.7–0.9. Breast CTV demonstrated good inter‐observer variability scores (mean DSC 0.9) for both pre‐ and post‐workshop. Post‐workshop observer delineated cervix GTV was smaller than pre‐workshop by 26.9%. Conclusion A radiologist‐led workshop did not significantly reduce inter‐observer variability in volume delineation for the three clinical sites. However, some improvement was noted in delineation of breast CTV, seroma volumes and cervix GTV.